2023
DOI: 10.1002/jsfa.12913
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, modification, and characterization of native litchi seed (Litchi chinesis Sonn.) starch

Abstract: BackgroundLitchi seeds, owing to their high starch content, have the potential to serve as a valuable non‐conventional source of starch with versatile applications. This study aimed to optimize the extraction of native litchi seed and its modification using citric acid. Response surface methodology was used to determine the optimal combination of independent variables; extraction temperature (30 – 60 ° C) and extraction time (4‐20hours) for the attainment of maximum starch yield (%). Starch was then chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…JSS presented with a higher increase in final viscosity than CCS (Figure 2b); this behavior is related to the amount of amylose released, which tends to form a network with water [10,38]. Even though JSS has less amylose than CCS, the structural characteristics could be different.…”
Section: Characteristics Properties and Potential Applications Of Jin...mentioning
confidence: 96%
See 3 more Smart Citations
“…JSS presented with a higher increase in final viscosity than CCS (Figure 2b); this behavior is related to the amount of amylose released, which tends to form a network with water [10,38]. Even though JSS has less amylose than CCS, the structural characteristics could be different.…”
Section: Characteristics Properties and Potential Applications Of Jin...mentioning
confidence: 96%
“…The sediment weights (W 1 , gel) were recorded. Both SP and WS were estimated with Equations ( 1) and (2), respectively [1,10].…”
Section: Swelling Power (Sp) and Water Solubility (Ws)mentioning
confidence: 99%
See 2 more Smart Citations
“…Hernández-Carmona et al [63], for example, observed that increasing the concentration of ascorbic acid from 1% to 5% w/v increased the extraction of starch from 23.8% to 32.5%. Kaur et al (Table 3, Entry 2) [64] found that the highest starch recovery from biomass was obtained using a temperature of 30 • C and an extraction time of 11 h; moreover, the modification of extracted starch with citric acid caused a depletion of swelling power, solubility, and amylose content, coupled with an increase in water absorption capacity. Cassava peel yielded more starch compared to bagasse (Table 3, Entry 3) [65], and this starch was also more thermostable.…”
Section: Starch: a Promising Biopolymer For Agricultural Applicationsmentioning
confidence: 99%